Effect of synthetic nano-hydroxyapatite as an alternative phosphorus source on growth and phosphorus nutrition of lettuce (Lactuca sativa L.) plant. (28th May 2018) - Taşkın, Mehmet Burak; Şahin, Özge; Taskin, Havva; Atakol, Orhan; Inal, Ali; Gunes, Aydin
ABSTRACT: Phosphorus (P) is one of the least available mineral nutrients to the plants in calcareous and alkaline soils. In this study, we investigated the synthesis, characterization and use of synthetic nano-hydroxyapatite (NHA), P uptake by plants as well as its residual effects. Soluble P source (H3 PO4 ) was also included as treatment for comparison. NHA prepared by wet chemical techniques, characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and elemental dispersive X-ray (EDX) analysis. NHA and H3 PO4 were applied at a rate of 200 mg kg −1 to find out their effects on phosphorus nutrition and growth of lettuce on the low and high calcareous soil. In addition to this, residual effects of NHA and H3 PO4 were also determined for lettuce plants grown after first lettuce plants in the both soil. Dry weights of the first and second lettuce plants grown in low and high calcareous soil were significantly increased by applied phosphorus regardless of the source. NHA seems to be more effective than that of ordinary phosphorus source (H3 PO4 -P) on growth and P concentration of the lettuce plants. The promising results of this study needs to be supported with long term field studies regarding the uptake, translocation and interactions of nano-P with the other elements.